Analisis Kebijakan Mutasi Pegawai Negeri Sipil Eselon II : (Studi Pemerintah Provinsi Maluku Utara Tahun 2014) - Ibrahim, Alfis; Pribadi, Ulung (Journal of Governance and Public Policy, 2015)
Program relations employees well-ordered very useful for organization and pegawai. Internal employees itself isactivity management human resources that deals with displacement or mutation employees in organization..The problemwas appointed in this research first, where do policy mutation civil servants echelon ii by the provincial governmentsNorth Maluku. Second, factor that influences mutation civil servants by the provincial governments NorthMaluku. Data collection techniques used is a questionnaire, the interview, and observation. While the kind of data isthe primary and secondary data.Totaling population and samples to research is 60 people this research in a qualitativedescriptive using analysis.This research result indicates that mutations not only to civil servants received a lot ofchallenges new and a new task as set already.But mutations are also efforts of the governor regulation, and mutationcivil servants be consistent with act of state civil apparatus in 2014, about authority removal, shifting,dismissal of civilservants. Besides mutation civil servants in government positions of government province by North Maluku it was stillfar from expectation, because there were uncertainty the law and does not consistency of mutation requirements andremoval of office.